2021
DOI: 10.4314/ahs.v21i3.23
|View full text |Cite
|
Sign up to set email alerts
|

Diphtheria serology in adults in Central Java and East Java, Indonesia: the importance of continuous diphtheria vaccination

Abstract: Background: Vaccination increase immunity against diphtheria, yet will decrease by aging. Therefore, boosters are needed to be done regularly. Objectives: This study aims to determine the immunity to diphtheria for the population of 16 years old and above. Methods: The sample of study were 295 collected blood serums by Riskesdas project in 2013, the criteria was above 15 years of age and originating from the Provinces of Central Java or East Java inclusively. Immunity assessment was based on antibo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…The preliminary study data obtained indicates a high level of protection of the subjects from the indicated risk groups from diphtheria (99.5% (95% CI: 97.2–99.9%) of protected subjects among the examined cohort of pregnant women and 99.1% (95% CI: 97.8–99.8%) of protected subjects among the examined cohort of healthcare professionals) and tetanus (91.5% (95% CI: 86.7–95.0%) and 96.9% (95% CI: 94.9–98.3%) of protected subjects, respectively). This is comparable to the results obtained by researchers in other countries when testing for diphtheria and tetanus seroprevalence in the same risk groups ( 20 , 21 ), or among adults, regardless of their profession ( 22 , 23 ).…”
Section: Discussionsupporting
confidence: 89%
“…The preliminary study data obtained indicates a high level of protection of the subjects from the indicated risk groups from diphtheria (99.5% (95% CI: 97.2–99.9%) of protected subjects among the examined cohort of pregnant women and 99.1% (95% CI: 97.8–99.8%) of protected subjects among the examined cohort of healthcare professionals) and tetanus (91.5% (95% CI: 86.7–95.0%) and 96.9% (95% CI: 94.9–98.3%) of protected subjects, respectively). This is comparable to the results obtained by researchers in other countries when testing for diphtheria and tetanus seroprevalence in the same risk groups ( 20 , 21 ), or among adults, regardless of their profession ( 22 , 23 ).…”
Section: Discussionsupporting
confidence: 89%
“…Diphtheria, one of the VPDs, mainly includes respiratory diphtheria and cutaneous diphtheria, affecting respiratory mucosa and skin. The global case fatality rate is around 10%, and it keeps in severe cases ( 3 ). With diphtheria vaccination, the incidence of disease has decreased dramatically ( 4 ).…”
Section: Introductionmentioning
confidence: 99%